Carbamazepine Induces Focused T Cell Responses in Resolved Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis Cases But Does Not Perturb the Immunopeptidome for T Cell Recognition - Mifsud, Nicole A.; Illing, Patricia T.; Lai, Jeffrey W.; Fettke, Heidi; Hensen, Luca; Huang, Ziyi; Rossjohn, Jamie; Vivian, Julian P.; Kwan, Patrick; Purcell, Anthony W. (Frontiers in Immunology, 2021)
Antiseizure medications (ASMs) are frequently implicated in T cell-mediated drug hypersensitivity reactions and cause skin tropic pathologies that range in severity from mild rashes to life-threatening systemic syndromes. During the acute stages of the more severe manifestations of these reactions, drug responsive proinflammatory CD8+ T cells display classical features of Th1 cytokine production and cytolysis. These T cells may be found locally at the site of pathology (e.g. blister cells/fluid), as well as systemically (e.g. blood, organs). What is less understood is the long-lived immunological effects of the memory T cell pool following T cell-mediated drug hypersensitivity reactions. In this study, we examine the ASM carbamazepine (CBZ) and the CBZ-reactive memory T cell pool in patients who have a history of Stevens-Johnson syndrome (SJS) from 3-to-20 years following their initial adverse reaction. We show that in vitro drug restimulation of CBZ-specific CD8+ T cells results in a proinflammatory profile and produces a mainly focused, yet private, T cell receptor (TCR) usage amongst human leukocyte antigen (HLA)-B*15:02-positive SJS patients. Additionally, we show that expression of these CBZ-specific TCRs in a reporter cell line, lacking endogenous abTCR, recapitulates the features of TCR activation reported for ASM-treated T cell lines/clones, providing a useful tool for further functional validations. Finally, we conduct a comprehensive evaluation of the HLA-B*15:02 immunopeptidome following ASM (or a metabolite) treatment of an HLA-B*15:02-positive cell line and show a lack of perturbation in the peptide repertoire. Collectively, this study shows that CBZ-specific T cells activate via the drug and the HLA-B*15:02 scaffold and that reactivation of memory T cells results in a focused private TCR profile in patients with resolved disease.